GNC–app: A new Cytoscape app to rate gene networks biological coherence using gene–gene indirect relationships. (April 2018) - Díaz-Montaña, Juan J.; Gómez-Vela, Francisco; Díaz-Díaz, Norberto
Graphical abstract: Highlights: A new app to rate the biological coherence of a gene network by comparing it with any gold-standard. The app uses the indirect relationships to perform gene network assessment. The app is more efficiently than original GNC due to the dramatic reduction of computational cost. The app integrates with Cytoscape's core features to perform a deeper analysis of the network. Abstract: Motivation: Gene networks are currently considered a powerful tool to model biological processes in the Bioinformatics field. A number of approaches to infer gene networks and various software tools to handle them in a visual simplified way have been developed recently. However, there is still a need to assess the inferred networks in order to prove their relevance. Results: In this paper, we present the new GNC-app for Cytoscape. GNC-app implements the GNC methodology for assessing the biological coherence of gene association networks and integrates it into Cytoscape. Implemented de novo, GNC-app significantly improves the performance of the original algorithm in order to be able to analyse large gene networks more efficiently. It has also been integrated in Cytoscape to increase the tool accessibility for non-technical users and facilitate the visual analysis of the results. This integration allows the user to analyse not only the global biological coherence of the network, but also the biological coherence at the gene–gene relationship level. It also allows the user to leverage Cytoscape capabilities as well as its rich ecosystem of apps to perform further analyses and visualizations of the network using such data. Availability: The GNC-app is freely available at the official Cytoscape app store:http://apps.cytoscape.org/apps/gnc .